Heart rate and blood pressure measurement based on photoplethysmogram signal using fast Fourier transform. (July 2022) - Sharma, Ashish; Tanwar, Rahul Singh; Singh, Yash; Sharma, Ajay; Daudra, Shaktiraj; Singal, Gaurav; Gadekallu, Thippa Reddy; Pancholi, Sidharth
Abstract: Physiological measurements are an important parameter of a person's health. Therefore, we must take the information about our body's physiological measurements to remain updated with our health status. There are a huge number of patients and few physicians in this world. This is creating an imbalance in the health industry. To cope with the imbalance, there is a high need for an application that allows users to monitor their health in case of an emergency. This paper proposes novel algorithms and methods to measure a person's heart rate and blood pressure using photoplethysmography (PPG) signals. PPG signals are captured through the Android cell phone flashlight camera. The heart rates calculated from the android application are compared with the digital blood pressure and heart rate monitor medical device, we achieved an encouraging accuracy of nearly 98%. Graphical abstract: Highlights: We have proposed a sliding window average based on heartbeat detection algorithms and architecture. FFT-based decomposition of signals and finding local and global amplitude to detect the correct heartbeat signal. Our proposed soluation is more accurate and faster than previous techniques to measure heartbeat and blood pressure.